PALAEOASSOCIA as a methodological tool for phytosociological analyses is further developed - Otto Brinkkemper; Mans Schepers; Onno Van Tongeren (Vegetation History and Archaeobotany, 2024)
The earlier version of PALAEOASSOCIA involved a considerable input of manual labour in sorting species tables with association data to identify plant communities that could have been present. A large archaeobotanical dataset from the site of Best (The Netherlands) was used to judge whether this manual sorting results in subjective results. As these were found, we developed a fully automatic version of PALAEOASSOCIA, including this sorting process. Likelihood clustering with prior probability yielded the highest number of associations recovered from four samples, and was therefore chosen as the optimal clustering method. The sorted tables are automatically converted to syntaxonomical groups. The hierarchical level of these groups can be pre-defined by the user of the program. Syntaxa that are highly improbable geographically cannot be ruled out a priori, but need to be removed manually. PALAEOASSOCIA is not meant to replace other methods of ecological interpretations of archaeobotanical data, but instead as a tool to obtain a more detailed result.

A meta-analysis of the presence of crop plants in the Dutch and German terp area between 700 bc and ad 1600 - Mans Schepers; Karl-Ernst Behre (Vegetation History and Archaeobotany, 2023)
There is a long tradition of archaeobotanical research in and around the dwelling mounds, known as terps or Wurten (among other names), along the Wadden Sea coast. The present paper presents an overview of crop plants retrieved from 1,389 samples, from a total of more than 100 sites, spanning the Iron Age to the Early Modern Period. Traditionally, the area has been more associated with animal husbandry than with crop farming. The crops that do occur are often mentioned in the form of a simple list, which is presented as being constant through time and space. Despite the large number of samples available, an overview looking at the potential diversity in crop plant composition in the area across time and space has been lacking until now. The present paper shows clear trends over time, starting long before the permanent embanking of the Wadden Sea salt marshes.

The common and the rare: a review of Early Modern Dutch plant food consumption based on archaeobotanical urban cesspit data - Merit M. A. Hondelink; Mans Schepers (Vegetation History and Archaeobotany, 2020)

Roman impact on the landscape near castellum Fectio, The Netherlands - Valerie van den Bos; Otto Brinkkemper; Ian D. Bull; Stefan Engels; Tom Hakbijl; Mans Schepers; Marieke van Dinter; Guido van Reenen; Bas van Geel (Vegetation History and Archaeobotany, 2014)

An objective method based on assemblages of subfossil plant macro-remains to reconstruct past natural vegetation: a case study at Swifterbant, The Netherlands - Mans Schepers; J. F. Scheepens; René T. J. Cappers; Onno F. R. van Tongeren; Daan C. M. Raemaekers; Renée M. Bekker (Vegetation History and Archaeobotany, 2013)